The benefits and harms of therapeutic exercise on physical and psychosocial outcomes in people with multimorbidity: Protocol for a systematic review. (8th May 2020) - Bricca, Alessio; Harris, Lasse K; Saracutu, Madalina; Smith, Susan M; Juhl, Carsten B; Skou, Søren T
Aim: The aim of this study is to investigate the benefits and harms of therapeutic exercise in people with multimorbidity defined as the combination of two or more of the following conditions: knee and hip osteoarthritis, hypertension, diabetes type 2, depression, heart failure, ischaemic heart disease and chronic obstructive pulmonary disease, by performing a systematic review of randomized controlled trials (RCTs). Methods: This study will be performed according to the recommendations from the Cochrane Collaboration and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We will search for RCTs investigating the effect of therapeutic exercise in multimorbidity, as defined above, in MEDLINE, EMBASE, CENTRAL and CINAHL from 1990. Cochrane reviews on the effect of therapeutic exercise for each of the aforementioned conditions and references of the included studies will be checked for eligible studies and citation tracking will be performed in Web of Science. We will assess the risk of bias of the included studies using the Cochrane 'Risk of Bias Tool' 2.0 and the Grading of Recommendations Assessment, Development and Evaluation assessment for judging the overall quality of evidence. Meta-analyses will be performed, if possible, using a random-effects model as heterogeneity is expected due to differences in interventions and participant characteristics and outcome measures. Subgroup and meta-regression analyses will be performed to explore potential predictors of outcomes. Dissemination: The results of this systematic review will be published in a peer-review journal, presented at national and international conferences and made available to end users via infographics, podcasts, press releases and videos.